Environmental compatibility of the fishmeal industry in Paracas-Pisco - Cabrera Carranza, Carlos Francisco (1999)
Concerns about environmental problems have increased considerably in recent times. Interest has been given at all levels of government, non-governmental organizations, scientific and technical groups, etc. due to the interrelation between the natural environment and the anthropic environment that are feasible to create risky contingencies. These are approached from three variables: the agent (nature and / or man), the time (before, during and after the event) and lastly, the effects it produces. From an environmental perspective, the industrialization of fishmeal has a significant impact on the ecosystem in which it operates, also affecting the well-being and health of people. This industry is an activity that generates foreign exchange, is a source of employment and contributes to the development of Peru, taking advantage of a resource that is relatively abundant in the Peruvian marine ecosystem. The present study is framed in the Paracas district, (13 ° 46 '52 "S, 76 ° 14' 19" W), Pisco province, Ica department, Peru, located 249 km south of Lima.